Analysis of Challenges and Optimization Strategies for Supply Chain Management at Aplus Market Stores through a Supply Chain Management (SCM) Approach - Wahyu Triono Putra; D. Dailami; S. Sahara; Mhd Riefzky Naufal; Risma Agustina; Rico Armanda Marpaung; Lukman Nul Hakim (Manunggal Halim Jaya, 2026)
Supply chain management is a crucial element in improving the efficiency and effectiveness of company operations, including managing the distribution of basic necessities. This study aims to analyze the supply chain management strategies implemented at Aplus Market Stores in addressing supply challenges, such as price fluctuations, government policies, and other external disruptions. The research method used was a qualitative approach using observation and in-depth interviews with store owners and employees. The results indicate that the implementation of structured Supply Chain Management can reduce delivery delays, avoid excess or shortages of stock, and improve procurement accuracy. In conclusion, strengthening coordination with suppliers and using a more accurate stock recording system has proven effective in maintaining supply stability at Aplus Market Stores.